1998
DOI: 10.1093/humrep/13.7.1810
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection of ovarian benign cystic teratomas: experience with 84 cases

Abstract: Laparoscopic treatment of benign cystic teratoma of the ovary has been recommended following the study of relatively small numbers of patients. We reviewed our experience with a prospective ongoing protocol for the treatment of benign ovarian teratomas, between January 1990 and December 1996. Sonography established the diagnosis, and biochemical markers were used to screen for possible malignancy. Surgery consisted of resecting the cyst and conserving the ovary if appropriate. The resected cyst was aspirated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 16 publications
0
36
0
3
Order By: Relevance
“…Surgical options to treat teratomas are individualized by the possibility of chemical peritonitis and malignancy (3). The existence of giant mature ovarian teratomas, as suggested by the preoperative examination and operative inspection, advises the excision of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical options to treat teratomas are individualized by the possibility of chemical peritonitis and malignancy (3). The existence of giant mature ovarian teratomas, as suggested by the preoperative examination and operative inspection, advises the excision of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Teratomas most commonly arise in the gonads but have also been found in the anterior mediastinum, retroperitoneum and gastrointestinal tract (1). Several studies have reported that laparoscopic approaches are generally accepted in normal cases for their minimal invasiveness, fewer complications and quicker recovery (2)(3)(4). The evident cosmetic advantage of this technique for young women is also noted.…”
Section: Introductionmentioning
confidence: 99%
“…Teratomas generally arise from the gonads but have also been found in anterior mediastinum, retroperitoneum and gastrointestinal tract [2][3][4][5] . They typically occur at reproductive age in second to third decade of life, however it can occur in any age from one to 90 years 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Maligniteye dönüşüm oranı oldukça nadirdir ve en sık malign dönüşüm skuamöz hücreli karsinomdur (2,3).…”
Section: Introductionunclassified